Android-Based Prototype for Early Tuberculosis Detection via Clinical Symptoms - Liena Sofiana; Suci Musvita Ayu; Jefree Fahana; Moh. Irma Sukarelawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Background: Health technology has enormous potential for preventing and curing TB. As a result, this research aims to create a prototype of an early detection tool for clinical symptoms based on Android. Methods: The Cure-TB application prototype is being developed through Research and Development, type 4D (Define, Design, Develop, and Disseminate). A total of 45 potential users evaluated the Cure-TB prototype utilizing 10 System Usability Scale (SUS) criteria. The SUS scale employs a five-point scale ranging from 1 (Strongly Disagree) to 5 (Strongly Agree). The SUS scale's item dependability is 0.91, and its Cronbach's alpha coefficient is 0.68. Prospective users' test results were examined using Rasch modelling approaches such as Logit Value of Person (LVP), Logit Value of Item (LVI), and Wright map. Results: Cure-TB contains seven main elements that help in the treatment of tuberculosis. The seven elements provided support the role of each user, which includes patients, health staff, and the general public. The SUS test findings showed a score of 75, meaning that the Cure-TB application received good feedback from most prospective users. Feedback from users that it takes time to get used to the various features provided. Conclusion: The Android-based Cure-TB application provides a unique option for early tuberculosis identification, enhancing patient treatment compliance and monitoring patients' side effects and nutritional condition.